Application of Hosomi-Sakurai allylation reaction in total synthesis of biologically active natural products - Akwensi, Justice; Kumah, Robert T.; Osei-Safo, Dorcas; Amewu, Richard K. (Frontiers in Chemistry, 2025)
The Hosomi–Sakurai allylation reaction has been widely applied in the total synthesis of biologically active natural products, especially in synthesising complex polycyclic compounds containing multi-stereogenic centres since its discovery in 1976. The Hosomi-Sakurai allylation is the allylation of ketones and aldehyde with nucleophilic allylsilanes catalyzed with Lewis acid mainly used to extend the C-C bond in a molecule and also create a new site for manipulation due to the facile transformation of the pi (π) bond at the end of its chain. This review highlights only portions of natural product synthetic works that feature the Hosomi-Sakurai allylation reaction or its modification as a key transformation in the synthetic route.